Analisis Kerusakan Komponen Inverter Gate 3 pada Eskalator Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Kurniawanto, Hari; Suwono, Niedya Inten; Ramadhan, Habibie Nur Hidayah; Bayhaky, M.Yanief Satria; Saputra, Agus Gede Dhananjaya; Fachrozie, Hafiz Adhilfi (Program Studi Teknik Mekanikal Bandar Udara, 2023)
Escalator is one of the common vertical transportation tools for the aviation industry in the world and Indonesia. To drive the escalator stairs with high efficiency and reliability, inverters are used as a key component in its drive system, responsible for regulating the motor speed and ensuring efficient operation. This study aims to identify and analyze the problems associated with inverters in escalators and their impact on the performance and reliability of the escalator system as a whole. The method carried out by the quantitative method is by collecting the required data ranging from observation, direct measurement, interviews, and literature studies to airport documents. The results showed that the factor causing inverter damage was a sudden power outage by PLN. When the electricity is on, there is a shock voltage above 420 volts which causes overheating in the inverter. To prevent inverter damage, a remote monitoring tool is needed, namely remote monitoring with IoT (Internet of Things) to overcome overheating problems on escalators. This research will thoroughly discuss the damage to the gate 3 inverter component on the escalator of Jenderal Ahmad Yani Semarang International Airport along with the problems and how to solve them.